1980
DOI: 10.1073/pnas.77.12.7415
|View full text |Cite
|
Sign up to set email alerts
|

Detection and isolation of type C retrovirus particles from fresh and cultured lymphocytes of a patient with cutaneous T-cell lymphoma

Abstract: Retrovirus particles with type C morphology were found in two T-cell lymphoblastoid cell lines, HUT 102 and CTCL-3, and in fresh peripheral blood lymphocytes obtained from a patient with a cutaneous T-cell lymphoma (mycosis fungoides).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

12
2,169
1
88

Year Published

1982
1982
2005
2005

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 4,474 publications
(2,270 citation statements)
references
References 27 publications
12
2,169
1
88
Order By: Relevance
“…5 Subsequent seroepidemiologic, morphologic, and molecular studies confirmed that HTLV-1 is the causative agent of ATLL cases that had (Diff-Quik stain, original magnification ϫ600).…”
Section: Discussionmentioning
confidence: 91%
“…5 Subsequent seroepidemiologic, morphologic, and molecular studies confirmed that HTLV-1 is the causative agent of ATLL cases that had (Diff-Quik stain, original magnification ϫ600).…”
Section: Discussionmentioning
confidence: 91%
“…The first description of HTLV-I came after the discovery of the human T-cell growth factor (interleukin-2; IL-2) [2], allowing long-term in vitro culture of T cells and establishment of T-cell lines from a patient with a cutaneous T-cell lymphoma (CTCL) [3]. Soon after, this virus was identified as the etiological agent of ATLL [4], and the term ''HTLV-I'' was adopted.…”
Section: Discovery and Epidemiologymentioning
confidence: 99%
“…[1][2][3] HTLV-I-mediated T-cell transformation presumably arises from multiple oncogenic processes in which the virus induces chronic T-cell proliferation, resulting in accumulation of genetic defects and dysregulated growth of infected cells. Although the mechanisms of transformation and leukemogenesis are not yet fully elucidated, the viral protein Tax is thought to play a crucial role in these processes.…”
mentioning
confidence: 99%